The actin genes of Drosophila: a dispersed multigene family. - Fyrberg, E.A.; Kindle, K.L.; Davidson, N.; Kindle, K.L. (Cell, 1980)
We have initiated a study of the organization and expression of the actin genes of D. melanogaster. Using actin gene-specific probes from both chicken and Dictyostelium sources, a clone--denoted lambda DmA2--containing a Drosophila actin gene has been isolated from a representative library of Drosophila genomic DNA cloned in the lambda bacteriophage vector, Charon 4. Southern blotting experiments reveal that there is only one actin structural gene contained in the 17.5 kb Drosophila insert of lambda DmA2 and that the sequences immediately flanking the structural gene are single copy. Observations by electron microscopy of the R loop structures formed by hybridizing total cytoplasmic poly(A)+ RNA from Drosophila embryos to an appropriate subcloned segment of lambda DmA2 indicate that the gene consists of an approximately 70-170 nucleotide leader sequence encoding the 5' portion of the mature mRNA, a 1.65 kb intervening sequence not present in the mRNA and a 1.55 kb sequence containing the major portion of the gene. Using genomic blots with actin-specific probes derived from lambda DmA2, we show that there are six actin genes per haploid Drosophilia genome. They direct the synthesis of three major size classes of mRNA. Using in situ hybridization, the six genes have been localized to six widely dispersed sites on the polytene chromosomes; the locus for lambda DmA2 is 5C on the X chromosome. In vitro translation of mRNA selected hybridization by a DNA segment specific to lambda DmA2 suggests that this particular gene codes for one of the cytoplasmic actin polypeptides.